Criteria for assessing the speed of movement in young men in rowing on kayaks - Volodymyr Bogush; Sergiy Getmantsev; Konstantin Bogatyirev; Irina Koloskova; Olga Sokol; Oksana Reznichenko (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to develop quantitative criteria for assessing the physical quality of the speed and its constituent elements for modeling the training process in rowing on kayaks. Material & Methods: young men, specializing in rowing on kayaks, differing in age and sports qualification were examined. We have studied the tempo, time and speed of one motion, the frequency of movements, as well as sensorimotor responses to sound and light stimuli, according to the method of measuring the effect of the training action developed by us. The testing process simulates the typical conditions of training and competitive activity and evaluates performance of the task. Results: on the basis of complex studies of physical quality indicators of rapidity and constituent elements, criteria have been developed for their evaluation for young men of different ages in sports qualification who are engaged in rowing on kayaks. The proposed method of research and comparative analysis of mean values, as well as relative deviations of physical fitness indicators of surveyed athletes from model characteristics may indicate the functional preparedness of oarsmen. Conclusion: the conducted research made it possible to ascertain the sufficient effectiveness of the method developed by us for measuring the effect of a training action for determining the physical quality of the speed of athletes specializing in rowing on kayaks, which makes it possible to recommend it for practical use in training sessions.